Preliminary Investigation of Association Between Sanitation and Water Contamination by Cryptosporidium at Livestock Area in Jember - Nurdian, Yudha; Fitriyah, Ainun Nadiratul; Rachmawati, Dwita Aryadina; Yunita Armiyanti (Nursing and Health Sciences Journal (NHSJ), 2024)
Cryptosporidium sp. is one of the waterborne protozoa involving water as the main medium of transmission causing cryptosporidiosis in animals and humans and its presence is influenced by various things including hygiene and sanitation of the community. This cross-sectional study aims to determine the association between the implementation of the community-led total sanitation and the presence of Cryptosporidium oocysts in clean water sources. The research was conducted from October 2020 to June 2021 in Sukokerto Village, Sukowono, Jember Regency. The data were obtained from interview with the respondents using structured questionnaires. The presence of oocysts was examined by microscopic observations with sedimentation methods and Modified Ziehl=Neelsen staining, and the data were analyzed using Spearman rho statistical test. The results showed that there were 12 (20.3%) household with good category at the implementation of community-led total sanitation, 28 (47.5%) household with moderate category, and 19 (32.2%) household with poor category. The presence of Cryptosporidium oocysts was found in 6 (10.2%) samples of clean water sources. The results of statistical tests with Spearman rho showed a p-value=0.098, so that there was no significant association between the implementation of community-led total sanitation and the presence of Cryptosporidium oocysts in clean water sources in study location.